A high prevalence of blaOXA-48 in Klebsiella (Raoultella) ornithinolytica and related species in hospital wastewater in South West England. Issue 3 (8th March 2021) - Gibbon, Marjorie J.; Couto, Natacha; David, Sophia; Barden, Ruth; Standerwick, Richard; Jagadeesan, Kishore; Birkwood, Hollie; Dulyayangkul, Punyawee; Avison, Matthew B.; Kannan, Andrew; Kibbey, Dan; Craft, Tim; et al.
Abstract : Klebsiella species occupy a wide range of environmental and animal niches, and occasionally cause opportunistic infections that are resistant to multiple antibiotics. In particular, Klebsiella pneumoniae ( Kpne ) has gained notoriety as a major nosocomial pathogen, due principally to the rise in non-susceptibility to carbapenems and other beta-lactam antibiotics. Whilst it has been proposed that the urban water cycle facilitates transmission of pathogens between clinical settings and the environment, the level of risk posed by resistant Klebsiella strains in hospital wastewater remains unclear. We used whole genome sequencing (WGS) to compare Klebsiella species in contemporaneous samples of wastewater from an English hospital and influent to the associated wastewater treatment plant (WWTP). As we aimed to characterize representative samples of Klebsiella communities, we did not actively select for antibiotic resistance (other than for ampicillin), nor for specific Klebsiella species. Two species, Kpne and K . ( Raoultella ) ornithinolytica ( Korn ), were of equal dominance in the hospital wastewater, and four other Klebsiella species were present in low abundance in this sample. In contrast, despite being the species most closely associated with healthcare settings, Kpne was the dominant species within the WWTP influent. In total, 29 % of all isolates harboured the bla OXA-48 gene on a pOXA-48-like plasmid, and these isolates were almost exclusively recovered from the hospital wastewater. This gene was far more common in Korn (68 % of isolates) than in Kpne (3.4 % of isolates). In general plasmid-borne, but not chromosomal, resistance genes were significantly enriched in the hospital wastewater sample. These data implicate hospital wastewater as an important reservoir for antibiotic-resistant Klebsiella, and point to an unsuspected role of species within the Raoultella group in the maintenance and dissemination of plasmid-borne bla OXA-48 . This article contains data hosted by Microreact.